Statistical inference and Bayesian optimal life‐testing plans under Type‐II unified hybrid censoring scheme. (30th July 2020) - Sen, Tanmay; Bhattacharya, Ritwik; Pradhan, Biswabrata; Tripathi, Yogesh Mani
Abstract: This article describes the inferential procedures and Bayesian optimal life‐testing issues under Type‐II unified hybrid censoring scheme. First, the explicit expressions of expected number of failures, expected duration of testing, and Fisher information matrix for the unknown parameters of the underlying lifetime model are derived. Then, using these quantities, the Bayesian optimal life‐testing plans are computed in a subsequent section. A cost constraint D‐optimal optimization problem has been formulated, and the corresponding solution algorithm is provided to obtain optimal plans. Computational procedures are illustrated through numerical examples.